7y+4(y-8)=3(y+1)-2

Simple and best practice solution for 7y+4(y-8)=3(y+1)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y+4(y-8)=3(y+1)-2 equation:


Simplifying
7y + 4(y + -8) = 3(y + 1) + -2

Reorder the terms:
7y + 4(-8 + y) = 3(y + 1) + -2
7y + (-8 * 4 + y * 4) = 3(y + 1) + -2
7y + (-32 + 4y) = 3(y + 1) + -2

Reorder the terms:
-32 + 7y + 4y = 3(y + 1) + -2

Combine like terms: 7y + 4y = 11y
-32 + 11y = 3(y + 1) + -2

Reorder the terms:
-32 + 11y = 3(1 + y) + -2
-32 + 11y = (1 * 3 + y * 3) + -2
-32 + 11y = (3 + 3y) + -2

Reorder the terms:
-32 + 11y = 3 + -2 + 3y

Combine like terms: 3 + -2 = 1
-32 + 11y = 1 + 3y

Solving
-32 + 11y = 1 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-32 + 11y + -3y = 1 + 3y + -3y

Combine like terms: 11y + -3y = 8y
-32 + 8y = 1 + 3y + -3y

Combine like terms: 3y + -3y = 0
-32 + 8y = 1 + 0
-32 + 8y = 1

Add '32' to each side of the equation.
-32 + 32 + 8y = 1 + 32

Combine like terms: -32 + 32 = 0
0 + 8y = 1 + 32
8y = 1 + 32

Combine like terms: 1 + 32 = 33
8y = 33

Divide each side by '8'.
y = 4.125

Simplifying
y = 4.125

See similar equations:

| 2x+y=-83 | | 3z-18=15-5z | | -12+13=10+n | | x^2+dx+49=0 | | 36x^2+17x-35=0 | | 4+w=3 | | F(X)=7x^8-1x^4+1 | | 84=12s | | -w+2=-2w+7 | | -3x-7x=-12 | | -2+15=4b-4-3b | | 20+m+13+m=2 | | -5a+24+2a=7a-4a | | (8+5i)(2-5i)= | | X+12-(-4)=17 | | 12-2(x+1)=5 | | 8-3x+12=11 | | 0.3x-0.7x-27=1 | | 6x+10038=x-28483 | | 15-2x=41 | | -7(x-4)+8x=26 | | 2(r)-7=r+15 | | 11w-13w=4 | | 41-3n=2 | | 6x+9=15x | | n^2-3n-40= | | 9x-14=6x-13 | | -5n+3n=4n-5n | | x^2=x+25 | | y=17x+544 | | 7x+10=27 | | 6w+5-5w=8-3 |

Equations solver categories